Treatise on Basic Philosophy - Bunge, M. author. aut Link
XVI, 354 p.
Keywords: In this Introduction' we shall sketch the business of ontology, or metaphysics, and shall locate it on the map of learning. This has to be done because there are many ways of construing the word 'ontology' and because of the bad reputation metaphysics has suffered until recently - a well deserved one in most cases. 1. ONTOLOGICAL PROBLEMS Ontological (or metaphysical) views are answers to ontological ques tions. And ontological (or metaphysical) questions are questions with an extremely wide scope, such as 'Is the world material or ideal - or perhaps neutral?" 'Is there radical novelty, and if so how does it come about?', 'Is there objective chance or just an appearance of such due to human ignorance?', 'How is the mental related to the physical?', 'Is a community anything but the set of its members?', and 'Are there laws of history?'. Just as religion was born from helplessness, ideology from conflict, and technology from the need to master the environment, so metaphysics - just liketheoretical science - was probably begotten by the awe and bewilderment at the boundless variety and apparent chaos of the phenomenal world, i. e. the sum total of human experience. Like the scientist, the metaphysician looked and looks for unity in diversity, for pattern in disorder, for structure in the amorphous heap of phenomena - and in some cases even for some sense, direction or finality in reality as a whole.